Beyond surgery: clinical and economic impact of Enhanced Recovery After Surgery programs - Gaëtan-Romain Joliat; Olle Ljungqvist; Tracy Wasylak; Oliver Peters; Nicolas Demartines (BMC, 2018)
Abstract Background Enhanced Recovery After Surgery (ERAS) is a perioperative management based on multimodality and multidisciplinary work. ERAS has been shown to have important clinical and economic benefits, but its spread remains slow worldwide. Discussion This manuscript reviews the overall program benefits and focuses on important aspects for implementation well beyond surgery. Summary Implementation of ERAS pathways improves clinical outcomes and induces substantial economic gains. ERAS is the current surgical revolution.